Real time monitoring and controlling using Petri net algorithm for batch process plant / Mohamad Shaiful Osman - Osman, Mohamad Shaiful (2010)
Batch processing requires sequential , continuous and supervisory control and an effectively control total plant production. Petri net can be applied to event related process control in simulating, checking, debugging, and stating the quantitative deviations from the ideal solutions of any given continuous or discrete process as well as providing formal checking at all development stages from specification, design and implementation . This thesis searches the basic concepts and uses of the classical method Petri net algorithm in SCADA system to control and monitoring the process plant. This thesis has presented a framework for designing and implementing a Petri net based supervisory for online control systems with the human in the loop, that mean human as a operator to switch the operation or monitoring the process flow. In this thesis, Petri nets are used in designing the supervisory system that yield a compact graphical model for the real-time control system. Our approaches ensure that algorithm and real-time control operations give safety requirements for the system. This research is made for a system with fully integrated facilities for analyzing , monitoring and controlling of batch plant based on graph theory, batch modelling by means of Petri net algorithm and theory, control and configuration of SCADA system. Among the major benefits expected from the use of the algorithms are increasing the production, reducing cycle times, increasing yields and improved planning. Improved product quality achieved through greater repeatability of processing tasks from batch to batch and reduced the operating cost.